Effects of Anesthetic Agent Propofol on Postoperative Sex Hormone Levels - Kim, H.; Ku, S.-Y.; Kim, H. C.; Suh, C. S.; Kim, S. H.; Choi, Y. M. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Several studies have found anesthetic agents including propofol in ovarian follicular fluid. However, little is known about the effect of anesthetic agents on ovarian function. We aimed to investigate whether there were differences in the postoperative levels of sex hormones when propofol was used as the anesthetic agent. Methods: A retrospective review was done of 80 patients who underwent ovarian surgery, with 72 infertile women serving as controls. Patients were included in the study if their serum estradiol (E2) and follicle stimulating hormone (FSH) levels were measured during their first postoperative menstrual cycle. Results: Patients were grouped according to the use or non-use of propofol as follows: propofol group (n = 39) and non-propofol group (n = 41). The control group did not undergo surgery. Postoperative E2 levels did not differ between the three groups, but FSH levels were significantly higher in the patients who had undergone surgery compared to controls (p < 0.05). Post-hoc analysis of E2 and FSH levels in the propofol and non-propofol groups did not show any significant differences. Conclusions: The use of propofol did not result in any differences compared to other anesthetic agents in terms of postoperative sex hormone levels after gynecologic surgery. The type of anesthetic agent does not seem to affect the postoperative levels of female sex hormones.
Keywords: anesthesia; sex hormone; propofol